Development of a three-stage, cross-current air sparged mixer-settler for the purification of degraded PUREX solvent. Issue 8 (24th May 2023) - Anand P., Vishnu; Mishra, Satyabrata; Patra, Chayan; Gnanasoundari, J.; Sinha, P.K.; Mishra, Alok Kumar; Rajeev, R.; Desigan, N.; Velavendan, P.; Venkatesan, K.A.; Ananthasivan, K.
ABSTRACT: Tri-butyl phosphate (TBP) diluted with in n-dodecane (n-DD) is used as the solvent in PUREX process. Solvent degradation due to radiolysis and hydrolysis during the process is one of the major problems prevailing in reprocessing plants. This paper presents an overview of the design, fabrication, and performance evaluation of a three-stage, continuous, cross-current air sparged mixer-settler developed for purifying the degraded PUREX solvent using hydrazine carbonate. The developmental program consisted of various stages, starting with small-scale batch experiments to investigate the solvent treatment kinetics and phase separation characteristics, followed by design fabrication and performance evaluation of three-stage air sparged mixer-settler. The study on solvent treatment kinetics in a 1.6 L batch air sparged mixer using 1.5 M hydrazine carbonate showed that the concentration of di-butyl phosphate (DBP) in the simulated degraded solvent could be reduced from 8, 000 mg L −1 to less than 40 mg L −1 within 180 seconds. Performance evaluation of the three-stage air sparged mixer settler had shown that the DBP concentration in the simulated degraded organic phase could be brought down from 8, 000 mg L −1 to less than 15 mg L −1, and the equipment could process up to 60 L h −1 throughput with negligible phase entrainment.